Hemin Augments Growth and Hemoglobinization of Erythroid Precursors from Patients with Diamond-Blackfan Anemia - Eitan Fibach; Memet Aker (Anemia)
Diamond-Blackfan anemia (DBA) is congenital pure red-cell anemia due to a differentiation block in erythroid precursors. The disease is commonly caused by mutations in genes for ribosomal proteins. Despite the identification of disease causal genes, the disease pathogenesis is not completely elucidated. The ribosomal abnormalities are assumed to inhibit globin translation which may lead to excess free heme, stimulating a generation of free radicals and thereby damaging the precursors. We studied the effect of hemin (heme chloride) on cultured human erythroid precursors and found that contrary to aforementioned hypothesis, although hemin moderately stimulated free radicals, it did not cause apoptosis or necrosis. In erythroid precursors derived from DBA patients, hemin significantly stimulated growth and hemoglobinization. Thus, heme toxicity is unlikely to play a role in the pathophysiology of most DBA cases. Moreover, its beneficial effect in culture suggests a therapeutic potential.